Development of Spatial Model for Drinking Water Distribution in Mountain Villages in Lattakia Governorate - العبد إسماعيل; حسام سليمان (Latakia University Journal -Engineering Sciences Series, 2024)
The process of planning the infrastructure needed to manage drinking water in mountain villages is considered one of the complex processes facing decision-makers. This problem is evident in Syria in general and in Latakia Governorate in particular, and is represented by the spread of the phenomenon of thirsty mountain villages that lack drinking water service, as there are many standards contributing the planning process of drinking water management, and there is a clear discrepancy in the opinions of experts providing services in this field. To overcome this problem, this research is aiming to develop a mechanism for drinking water management in mountain villages, which includes combining between the Point allocation method (PAM) and GIS functions in order to produce several analytical maps reflecting our suggested criteria in the targeted area. The study resulted with producing a combined surface map for the potential areas of intervention, which identify priority locations for interventions to serve drinking water networks, which makes following this mechanism an essential stage when planning the necessary infrastructure for drinking water management according to the real stakeholders.